Work-Based Learning conceptual framework for effective incorporation of soft skills among students of vocational and technical institutions - Gimba, Dogara (Institute of Electrical and Electronics Engineers Inc., 2020)
The importance of soft skills has been recognized in most fields, hence, various companies make judgments on work and success evaluation based largely on employees' soft skills. Work-Based Learning (WBL), as an educational approach, can harness students' potential in soft skills. This investigation aimed to generate a conceptual framework for WBL to effectively integrate soft skills among students in technical colleges. A sample of 268 technical teachers was drawn from a population of 302 technical teachers from 22 public technical colleges within the study area using a stratified random sampling methodology based on the complex heterogeneity of the population. The study adopted structural equation modeling (SEM) to determine the nexus underlying the model, using analysis of moment of structures (AMOS) version 20. The study results discovered WBL preparation (planning and designing), supervision, and evaluation each have a positive impact on soft skill development among technical college students. By way of recommendation based on the study findings, the government should formulate and implement suitable policies to enhance planning and designing in WBL programmes, particularly, to address the needs of students for adequate incorporation of soft skills at technical colleges. Technical teachers could employ the WBL-recognized elements in integrating workplace experiences to successfully promote students' soft skills at technical colleges.